Einstein's big idea [videorecording (DVD)] ; Exploring space : the quest for life. - Johnstone, Gary, 1959-; Johnstone, Gary, 1959-; Johnstone, Gary, 1959-; Lithgow, John, 1945-; Bodanis, David (Discover magazine ultimate DVD library, 2006)
"Einstein's big idea" dramatizes how Einstein arrived at his 1905 discovery that the realms of matter and energy are linked. Reveals the roots of this breakthrough in the human stories of scientists Michael Farady, Antoine Lavoisier and Lise Maitner, whose innovative thinking across four centuries helped lead to E=mc², and ultimately unleashed the power of the atom.